Harmonization of Economics and Local Culture in the Frame of Suistainable Technological Innovation (Case Study of Ketoprak Atmodjo Budoyo in Kudur Village Pati Regency) - Citra Dewi , Lita; Maftukhah, Ida (KnE Social Sciences, 2020)
Indonesia is a superpower country in the field of culture (The United Nations Educational Scientific and Cultural-UNESCO). Culture can be way for the governments to improve the economy and reduce the gap in the industrial revolution 4.0. Undang-Undang nomor 5 tahun 2017 about promoting culture provides a platform for cultural development. In 2017 there were 141,732 people or equivalent with 11.38% belonging to the poor population, its means that there is 393,817 per capita per month in the poverty line in Pati. One of things that can help the economy is from the cultural sector, one of which is through the Ketoprak Cilik in Kudur village became the most influential Ketoprak Cilik in Pati, even this Ketoprak of Dalang Bowo Asmoro’s care had scented Pati district in an international art performance in Borobudur (www.kabarkotapati.com). This Kotoprak Cilik show still requires innovation related to industrial management, such as training and schedule management (Bowo Asmoro, 2019). Ketoprak Cilik consist of elementary and junior high school students. The training is held every Saturday and Monday at Kudur Village Hall. The Kudur Village office is equipped with a broad set of gamelan and stage areas that are useful for practicing Ketoprak Cilik performances. Ketopra Cilik as a Cultural is used to instill the spirit of love of local culture to the younger generation, this is a concrete step that encourages local people to jointly build the character of the young generation through culture. The results of the small ketoprak staging will be put into the village treasury to later help the community’s economy. With this can encourage the emergence of cultural economic collaboration in the village of Kudur-Pati. This study uses qualitative methods with interviews and references from various trusted sources. This paper examines more deeply how culture plays a role in improving the economy of the community and forming the character of Indonesia’s young generation. Keywords: Technology, Ketoprak Cilik, Economics